Cineastas e a formação da ANCINE (1999-2003) - Alvarenga, Marcus Vinícius Tavares de (2010)
This paper studies the Brazilian cinematography corporation political joint between 1999 and 2003. Starting from fiscal renounce model crisis in the national film production, wherein the dialog narrowing between filmmakers and the State led to the creation of the National Cinema Agency (Ancine), which generated the cinematographic group split concerning the agency link in the federal organization chart. In this context, I analyze the problems showed by the filmmakers to the sector sustainability and the possible solutions for this, including its limitations inside the scenario involving the cinematographic corporation, the State, the foreign distribution companies and national broadcasting companies. To do this research, it was used books, articles, internet site information, congress documents, federal legislation and interviews to set up the Brazilian cinema political joint development and its problems to execute the sector demands oriented to the sustainability.